Method for manufacturing a welded joint using a filler material for TIG welding

By adjusting the composition of the filling material for TIG welding, the generation of high-temperature cracks is suppressed, and the problem of high-temperature cracks when welding high-Mn steel is solved, and high-strength and excellent extremely low-temperature toughness welded joints in extremely low temperature environments are achieved, which meets the high-temperature Strength and high toughness requirements.

CN116529408BActive Publication Date: 2024-12-31JFE STEEL CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180082760.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-17
Filing Date
2021-12-16
Publication Date
2024-12-31
Estimated Expiration
2041-12-16

AI Technical Summary

Technical Problem

The prior art has high temperature cracks when welding high Mn steels, making it difficult to maintain the high strength and excellent extremely low temperature toughness of the welded joints under extremely low temperature environments.

Method used

The filling material for TIG welding is composed of C: 0.20 to 0.80%, Si: 0.15 to 0.90%, Mn: 15.0 to 30.0%, Cr: 6.0 to 15.0%, P: 0.030% or less, S: 0.030% or less, N: 0.120% or less, by forming Cr phosphides in the liquid phase of the welded metal, segregation and high-temperature cracks are suppressed, and the yield strength of 0.2% is ensured to be above 400MPa at room temperature, and the charpy impact at the test temperature -196°C The test absorption energy is above 28J.

Benefits of technology

It effectively suppresses the generation of high-temperature cracks during welding, ensures that the welded joints with high Mn-containing steel have high strength and excellent extremely low-temperature toughness, and meets significant industrial effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005051515360000151
    Figure GDA0005051515360000151
  • Figure GDA0005051515360000161
    Figure GDA0005051515360000161
Patent Text Reader

Abstract

The present invention provides a TIG welding filler material which is suitable as a welding material for high-Mn steel materials used in an extremely low temperature environment, suppresses the generation of high-temperature cracks during welding, and has excellent high-temperature crack resistance. A TIG welding filler material has the following composition: in terms of mass%, it contains C: 0.20-0.80%, Si: 0.15-0.90%, Mn: 15.0-30.0%, P: 0.030% or less, S: 0.030% or less, Cr: 6.0-15.0%, N: 0.120% or less. The balance is composed of Fe and unavoidable impurities. It should be noted that, as required, it may also contain one or two selected from Ni and Mo, and may also contain one or more selected from V, Ti and Nb. In addition, it may also contain one or more selected from Cu, Al, Ca and REM. As a result, it is possible to easily manufacture a weld joint portion that suppresses the occurrence of weld cracks during TIG welding, has excellent high-temperature crack resistance, and has high strength and excellent extremely low-temperature impact toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a filler material for TIG welding, and more particularly to a filler material for TIG welding having excellent high temperature crack resistance and suppressing the occurrence of high temperature cracks during welding, which is used for welding high Mn content steel materials used in extremely low temperature environments, and a method for manufacturing a welded joint using the filler material for TIG welding. Background Art

[0002] TIG welding is Tungsten Inert Gas welding, which is a welding method that uses tungsten, a non-consumable material, as an electrode rod, and melts other filler materials (welding rods) in an arc while blowing argon or helium, an inert gas, to block the air. According to this TIG welding, it can also be applied to various alloy steels, non-ferrous metals, etc., and even complex shapes can be welded, and excellent welding quality can be obtained, so it is used in welding all metals.

[0003] In recent years, environmental regulations have become stricter. In addition, liquefied natural gas (hereinafter referred to as LNG) is known as a clean fuel that does not produce air pollutants such as sulfur oxides because it does not contain sulfur, and its demand has increased. In addition, in order to transport or store the LNG, the container (tank) for transporting or storing the LNG needs to maintain excellent ultra-low temperature impact toughness at a temperature below -162°C, which is the liquefaction temperature of LNG.

[0004] Conventionally, aluminum alloys, 9% Ni steel, austenitic stainless steel, and the like have been used as materials for containers (tanks) and the like because of the need to maintain excellent cryogenic impact toughness.

[0005] However, aluminum alloys have low tensile strength, so the plate thickness of the structure needs to be designed to be large, and there is a problem of poor weldability. 9% Ni steel requires the use of expensive Ni-based materials as welding materials, which is economically disadvantageous. In addition, austenitic stainless steel has the problem of being expensive and having low base material strength.

[0006] In view of such problems, the application of high Mn steel (hereinafter also referred to as "high Mn steel") containing about 10% to about 35% Mn by mass has been studied recently as a material for containers (tanks) for transporting or storing LNG. High Mn steel has the following characteristics: it is an austenite phase even at extremely low temperatures, does not undergo brittle fracture, and has higher strength than austenitic stainless steel. Therefore, it is also desired to develop a welding method and welding material that can stably weld such high Mn steel.

[0007] In response to such a desire, for example, Patent Document 1 proposes a "high-strength weld joint portion having excellent ultra-low temperature impact toughness and a flux-cored arc welding wire used therefor". The flux-cored arc welding wire described in Patent Document 1 is a welding wire having a composition containing, by weight%, C: 0.15-0.8%, Si: 0.2-1.2%, Mn: 15-34%, Cr: 6% or less, Mo: 1.5-4%, S: 0.02% or less, P: 0.02% or less, B: 0.01% or less, Ti: 0.09-0.5%, N: 0.001-0.3%, TiO2: 4-15%, a total of one or more selected from SiO2, ZrO2 and Al2O3: 0.01-9%, a total of one or more selected from K, Na and Li: 0.5-1.7%, one or more selected from F and Ca: 0.2-1.5%, and the balance being Fe and other inevitable impurities. When welding is performed using the flux-cored arc welding wire described in Patent Document 1, it is possible to effectively obtain a weld joint having excellent low-temperature toughness of more than 28 J of Charpy impact test absorbed energy at a test temperature of -196°C and a high-strength weld joint having a room-temperature tensile strength of more than 400 MPa. In addition, by adjusting the welding wire composition to more than 1.5% Mo, it is possible to ensure a weld joint having excellent high-temperature crack resistance.

[0008] In addition, Patent Document 2 proposes a "solid wire for metal-metal arc welding". The solid wire for metal-metal arc welding described in Patent Document 2 is a wire having a composition containing, by mass%, C: 0.2-0.8%, Si: 0.15-0.90%, Mn: 17.0-28.0%, P: 0.03% or less, S: 0.03% or less, Ni: 0.01-10.00%, Cr: 0.4-4.0%, Mo: 0.01-3.50%, B: less than 0.0010%, N: 0.12% or less, and the balance being Fe and inevitable impurities. It should be noted that, as required, one or more selected from V, Ti and Nb, and one or more selected from Cu, Al, Ca and REM may be contained. When welding is performed using the solid wire for metal-arc welding described in Patent Document 2, it is possible to produce a welding wire that generates little smoke and has a high strength of 400 MPa or more at room temperature yield strength (0.2% yield strength) and an absorbed energy vE of 1.300 % in a Charpy impact test at a test temperature of -196°C. -196 The welded joint has a high strength of 28J or more and excellent ultra-low temperature impact toughness.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application No. 2017-502842

[0012] Patent Document 2: International Publication No. WO2020 / 039643 Summary of the invention

[0013] Problems to be solved by the invention

[0014] However, according to the research conducted by the present inventors, the techniques described in Patent Documents 1 and 2 have a problem in that high temperature cracks occur during welding.

[0015] The object of the present invention is to solve the problems of the above-mentioned prior art and to provide a filler material for TIG welding that can suppress the occurrence of high-temperature cracks during welding, is suitable as a welding material for high-Mn-containing steel used in an extremely low temperature environment, and can stably produce a weld joint portion having both high strength and excellent extremely low temperature toughness.

[0016] It should be noted that the so-called "high strength" here refers to the case where the room temperature yield strength (0.2% yield strength) of the deposited metal produced in accordance with the provisions of JIS Z 3111 is 400 MPa or more. "Excellent low temperature toughness" refers to the absorbed energy vE of the Charpy impact test of the deposited metal produced in accordance with the provisions of JIS Z 3111 at a test temperature of -196°C. -196 For the case of 28J or more.

[0017] Methods used to solve problems

[0018] In order to achieve the above object, the inventors first conducted an in-depth study on the factors that affect high temperature cracks during TIG welding of high Mn steel. As a result, it was found that as a factor causing high temperature cracks, segregation of P to the final solidified portion of the weld metal can be cited. In addition, it was found that if 6.0 mass% or more of Cr is contained in the composition of the filler, Cr phosphide is formed in the liquid phase of the weld metal, which has the effect of suppressing the segregation of P to the final solidified portion of the weld metal and also suppressing the occurrence of high temperature cracks.

[0019] In addition, the composition of the filler material for TIG welding required for making the deposited metal produced in accordance with the provisions of JIS Z 3111 a deposited metal having both the desired high strength and the desired excellent cryogenic toughness was studied. As a result, it was found that it is necessary to prepare a filler material for TIG welding having a composition in which C is adjusted to 0.20-0.80% and Si is adjusted to 0.15-0.90% in mass %, Mn is further adjusted to 15.0-30.0% and Cr is adjusted to a specific range of 6.0-15.0%, and P is reduced to 0.030% or less, S is reduced to 0.030% or less, and N is reduced to 0.120% or less, and a welded joint portion using the filler material for TIG welding is required.

[0020] The present invention has been completed as a result of further studies based on the above findings, and the gist of the present invention is as follows.

[0021] [1] A filler material for TIG welding having the following composition: in mass %, containing C: 0.20-0.80%, Si: 0.15-0.90%, Mn: 15.0-30.0%, P: 0.030% or less, S: 0.030% or less, Cr: 6.0-15.0%, N: 0.120% or less, and the balance being Fe and unavoidable impurities.

[0022] [2] The TIG welding filler material according to [1], further comprising, in addition to the above composition, one or two selected from the group consisting of Ni: 10.00% or less and Mo: 3.50% or less, in terms of mass %.

[0023] [3] The TIG welding filler material according to [1] or [2], further comprising, in addition to the above composition, one or more selected from the group consisting of V: ​​1.00% or less, Ti: 1.00% or less, and Nb: 1.00% or less, in terms of mass %.

[0024] [4] The TIG welding filler material according to any one of [1] to [3], further comprising, in addition to the above composition, one or more selected from the group consisting of Cu: 1.00% or less, Al: 0.100% or less, Ca: 0.010% or less, and REM: 0.020% or less, in terms of mass %.

[0025] [5] A method for manufacturing a welded joint, comprising performing TIG welding on a high Mn content steel material using the TIG welding filler material and a non-consumable electrode as described in any one of [1] to [4].

[0026] [6] The method for manufacturing a welded joint according to [5], wherein the Mn content in the composition of the high Mn content steel is 15.0 to 30.0% by mass.

[0027] [7] The method for manufacturing a welded joint portion according to [6], wherein the high Mn content steel has the following composition: in mass %, it contains C: 0.10-0.80%, Si: 0.05-1.00%, Mn: 15.0-30.0%, P: less than 0.030%, S: less than 0.030%, Cr: 2.5-15.0%, N: less than 0.120%, and the balance is Fe and unavoidable impurities.

[0028] [8] The method for manufacturing a welded joint according to [6] or [7], wherein the high Mn content steel material, in addition to the above composition, further contains, in terms of mass %, one or two selected from the group consisting of Ni: 10.00% or less and Mo: 3.50% or less.

[0029] [9] A method for manufacturing a welded joint according to any one of [6] to [8], wherein, in addition to the above composition, the high Mn content steel further contains, in terms of mass %, one or more selected from V: 2.00% or less, Ti: 1.00% or less, and Nb: 1.00% or less.

[0030]

[10] A method for manufacturing a welded joint according to any one of [6] to [9], wherein, in addition to the above composition, the high Mn content steel further contains, in terms of mass %, one or more selected from the group consisting of Cu: 1.00% or less, Al: 0.100% or less, Ca: 0.010% or less, and REM: 0.020% or less.

[0031] Effects of the Invention

[0032] The TIG welding filler material of the present invention can suppress high temperature cracking during TIG welding as a welding material for high Mn content steel and can easily produce a welded joint portion with high strength and excellent cryogenic toughness, which has a significant effect in industry. DETAILED DESCRIPTION

[0033] The present invention is a filler material suitable for TIG welding of high-Mn steel. If the filler material of the present invention is used, high-temperature cracks can be suppressed during TIG welding of high-Mn steels. In order to be able to cut test pieces, the test plate must be constrained or reversely strained in advance so that the angular deformation after welding does not exceed 5°. The groove shape is set to a V-shaped groove and is composed of a backing metal. Except for specially specified cases, welding is performed by flat welding, with 1 or 2 passes for the first and second layers, and 1 or 2 passes or more for the third layer and thereafter. The test piece after welding is not heat treated.

[0034] More preferably, the filler material of the present invention is a welding material in which the deposited metal produced by TIG welding in accordance with JIS Z 3111 has both high strength of 400 MPa or more in terms of 0.2% yield strength at room temperature and excellent low-temperature toughness of 28 J or more in the Charpy impact test at a test temperature of -196°C, and can produce a welded joint portion with high strength and excellent low-temperature toughness.

[0035] [TIG welding]

[0036] As mentioned above, TIG welding is a welding method that uses tungsten, which is a non-consumable material, as an electrode rod, and melts other filler materials in the arc while blowing argon or helium to block the air. This TIG welding can be applied to various alloy steels, non-ferrous metals, etc., and can weld even complex shapes, and can obtain excellent welding quality, so it is used in welding all metals.

[0037] As an example of the TIG welding method, a steel plate or steel material (plate thickness: 3 to 100 mm) as a base material is butt-jointed according to JIS Z3111 to form a 45° V-shaped groove, and a pure tungsten rod (3.2 mmφ) and a filler material (diameter 2.0 mmφ) are used as electrodes. Without preheating, the welding is carried out in a flat welding position at a current of 180 to 250 A (DCEN), a voltage of 10 to 15 V, a welding speed of 5 to 15 cm / min, a welding line energy of 0.7 to 4.0 kJ / mm, an interpass temperature of 100 to 150°C, an Ar shielding gas, and a gas flow rate of 10 to 25 L / min.

[0038] [Basic composition of filling materials]

[0039] The TIG welding filler material of the present invention has the following composition as a basic composition: in terms of mass%, it contains C: 0.20-0.80%, Si: 0.15-0.90%, Mn: 15.0-30.0%, P: 0.030% or less, S: 0.030% or less, Cr: 6.0-15.0%, N: 0.120% or less, and the balance is Fe and inevitable impurities. First, the reasons for limiting the composition of the basic composition are explained. It should be noted that, hereinafter, "%" in the composition means "mass %".

[0040] [C: 0.20~0.80%]

[0041] C is an element that has the effect of increasing the strength of the weld metal by solid solution strengthening. In addition, C stabilizes the austenite phase and improves the extremely low temperature impact toughness of the weld metal. In order to obtain such an effect, it is necessary to contain 0.20% or more. However, when it contains more than 0.80%, carbides precipitate, the extremely low temperature toughness decreases, and welding cracks (high temperature cracks) are easily generated during welding. Therefore, C is limited to the range of 0.20 to 0.80%. It should be noted that C is preferably 0.40% or more. Preferably, C is 0.60% or less. More preferably, C is 0.45% or more. More preferably, C is 0.55% or less.

[0042] [Si: 0.15-0.90%]

[0043] Si acts as a deoxidizer, has the effect of increasing the yield of Mn, increasing the viscosity of the molten metal, and stably maintaining the shape of the weld. In order to obtain such an effect, it is necessary to contain 0.15% or more. However, when it contains more than 0.90%, the extremely low temperature toughness of the weld metal is reduced. In addition, Si segregates during solidification, and a liquid phase is generated at the interface of the solidification unit, which reduces the high temperature crack resistance. Therefore, Si is limited to the range of 0.15 to 0.90%. Preferably, Si is 0.20% or more. Preferably, Si is 0.70% or less. More preferably, Si is 0.30% or more. More preferably, Si is 0.60% or less.

[0044] [Mn: 15.0~30.0%]

[0045] Mn is an element that stabilizes the austenite phase at low cost, and in the present invention, it is necessary to contain 15.0% or more. When Mn is less than 15.0%, a ferrite phase is generated in the weld metal, and the toughness at extremely low temperatures is significantly reduced. On the other hand, when Mn exceeds 30.0%, excessive Mn segregation occurs during solidification, inducing welding cracks (high temperature cracks). Therefore, Mn is limited to the range of 15.0 to 30.0%. It should be noted that Mn is preferably 18.0% or more. Mn is preferably 27.0% or less. More preferably, Mn is 20.0% or more. More preferably, Mn is 26.0% or less.

[0046] [P: 0.030% or less]

[0047] P is an element that segregates at grain boundaries and induces high temperature cracks. It is preferably reduced as much as possible, but it is permissible if it is 0.030% or less. Therefore, P is limited to 0.030% or less. It should be noted that excessive reduction leads to a rise in refining costs. Therefore, P is preferably adjusted to 0.003% or more. More preferably, P is 0.005% or more. More preferably, P is 0.020% or less.

[0048] [S: 0.030% or less]

[0049] S exists in the weld metal as MnS, which is a sulfide inclusion. MnS becomes the starting point of fracture, thus reducing the cryogenic toughness. Therefore, S is limited to 0.030% or less. It should be noted that excessive reduction leads to a rise in refining costs. Therefore, S is preferably adjusted to 0.001% or more. More preferably, S is 0.003% or more. More preferably, S is 0.020% or less.

[0050] [Cr: 6.0~15.0%]

[0051] Cr acts as an element that stabilizes the austenite phase at extremely low temperatures, thereby improving the extremely low temperature toughness of the weld metal. In addition, it has the effect of improving the strength of the weld metal. In addition, it also effectively plays a role in narrowing the temperature range of the solid-liquid coexistence region of the molten metal and suppressing the occurrence of high-temperature cracks, and also has the effect of suppressing high-temperature cracks caused by P by forming Cr phosphides in the liquid phase. In order to obtain such an effect, it is necessary to contain 6.0% or more. When Cr is less than 6.0%, the above effect cannot be ensured. On the other hand, when it contains more than 15.0%, Cr carbides are generated, resulting in a decrease in extremely low temperature toughness. Therefore, Cr is limited to the range of 6.0 to 15.0%. It should be noted that Cr is preferably greater than 7.0%. Cr is preferably 15.0% or less. More preferably, Cr is 8.0% or more. More preferably, Cr is 13.0% or less.

[0052] [N: 0.120% or less]

[0053] N is an element that is inevitably mixed in. Like C, it effectively contributes to the improvement of the strength of the weld metal, stabilizes the austenite phase, and contributes to the stable improvement of the extremely low temperature toughness. Such an effect becomes significant when it contains 0.003% or more. On the other hand, when it contains more than 0.120%, nitrides are formed and the low temperature toughness decreases. Therefore, N is limited to 0.120% or less. Preferably, N is 0.004% or more. Preferably, N is 0.080% or less. More preferably, N is 0.010% or more. More preferably, N is 0.060% or less.

[0054] [Optional Ingredients]

[0055] In the filler material of the present invention, the above components are basic components. However, in the present invention, based on the above basic composition, one or two selected from Ni: 10.00% or less and Mo: 3.50% or less may be selected as optional components as needed. In addition, one or two or more selected from V: 1.00% or less, Ti: 1.00% or less, and Nb: 1.00% or less may be selected. In addition, one or two or more selected from Cu: 1.00% or less, Al: 0.100% or less, Ca: 0.010% or less, and REM: 0.020% or less may be selected.

[0056] [Ni: 10.00% or less and Mo: 3.50% or less]

[0057] Both Ni and Mo are elements that strengthen austenite grain boundaries, and either or both may be contained as required.

[0058] [Ni: 10.00% or less]

[0059] Ni is an element that strengthens the austenite grain boundary, segregates at the grain boundary, and improves the cryogenic toughness. In addition, Ni also has the effect of stabilizing the austenite phase, so if the content is further increased, the austenite phase is stabilized, and the cryogenic toughness of the weld metal is improved. However, Ni is an expensive element, and when it is contained in excess of 10.00%, it becomes economically disadvantageous. Therefore, Ni is preferably limited to 10.00% or less. It should be noted that the range of 8.00% or less is more preferred. The range of 6.00% or less is further preferred.

[0060] [Mo: 3.50% or less]

[0061] Mo is an element that strengthens the austenite grain boundary, segregates at the grain boundary, and improves the strength of the weld metal. In addition, it also has the effect of improving the strength of the weld metal by solid solution strengthening. On the other hand, when it contains more than 3.50%, it sometimes precipitates as carbides and becomes the starting point of fracture, resulting in a decrease in extremely low temperature toughness. Therefore, Mo is preferably limited to a range of 3.50% or less. It should be noted that it is more preferably a range of 3.00% or less. It is further preferred that Mo is 1.00% or more. It is preferred that Mo is 3.00% or less.

[0062] [V: 1.00% or less, Ti: 1.00% or less, and Nb: 1.00% or less]

[0063] V, Ti and Nb are all elements that promote the formation of carbides and contribute to improving the strength of the weld metal, and one or more of them can be selectively contained as needed.

[0064] [V: 1.00% or less]

[0065] V is a carbide-forming element that precipitates fine carbides, which helps to improve the strength of the weld metal. In order to obtain such an effect, it is preferably contained at least 0.001%. However, when it is contained at more than 1.00%, the carbides coarsen and become the starting point of fracture, resulting in a decrease in cryogenic toughness. Therefore, when V is contained, V is preferably limited to 1.00% or less. Preferably, V is 0.002% or more. Preferably, V is 0.60% or less. More preferably, V is 0.005% or more. More preferably, V is 0.20% or less.

[0066] [Ti: 1.00% or less]

[0067] Ti is a carbide-forming element, which precipitates fine carbides and helps improve the strength of the weld metal. In addition, the precipitation of carbides at the solidification unit interface of the weld metal helps to suppress the occurrence of high-temperature cracks. In order to obtain such an effect, it is preferably contained at least 0.001%. However, when it contains more than 1.00%, the carbides coarsen and become the starting point of fracture, resulting in a decrease in extremely low temperature toughness. Therefore, when Ti is contained, Ti is preferably limited to less than 1.00%. Preferably, Ti is more than 0.002%. Preferably, Ti is less than 0.60%. More preferably, Ti is more than 0.005%. More preferably, Ti is less than 0.20%.

[0068] [Nb: 1.00% or less]

[0069] Nb is a carbide-forming element, and is an element that precipitates carbides and contributes to improving the strength of the weld metal. In addition, the precipitation of carbides at the solidification unit interface of the weld metal contributes to suppressing the occurrence of high-temperature cracks. In order to obtain such an effect, it is preferably contained at 0.001% or more. However, when it exceeds 1.00%, the carbides coarsen and become the starting point of fracture, resulting in a decrease in extremely low temperature toughness. Therefore, when Nb is contained, Nb is preferably limited to 1.00% or less. It should be noted that Nb is more preferably 0.002% or more. Preferably, Nb is less than 0.60%. More preferably, Nb is more than 0.005%. More preferably, Nb is less than 0.30%.

[0070] [Cu: 1.00% or less, Al: 0.100% or less, Ca: 0.010% or less, and REM: 0.020% or less]

[0071] Cu is an element that contributes to stabilization of austenite, Al is an element that contributes to stabilization of the weld bead shape, and Ca and REM are elements that contribute to improvement of workability, and one or more of them can be selectively contained as necessary.

[0072] [Cu: 1.00% or less]

[0073] Cu is an element that stabilizes the austenite phase. It stabilizes the austenite phase even at extremely low temperatures and improves the extremely low temperature toughness of the weld metal. In order to obtain such an effect, it is preferably contained at 0.01% or more. However, when it exceeds 1.00% and is contained in large quantities, segregation occurs during solidification, inducing high temperature cracks. Therefore, when Cu is contained, Cu is preferably limited to 1.00% or less. Preferably, Cu is 0.01% or more. Preferably, Cu is 0.60% or less. More preferably, Cu is 0.10% or less.

[0074] [Al: 0.100% or less]

[0075] Al acts as a deoxidizer and has an important role in increasing the viscosity of the molten metal and stably maintaining the shape of the weld bead. In addition, Al narrows the temperature range of the solid-liquid coexistence region of the molten metal, which helps to suppress the occurrence of high-temperature cracks in the weld metal. Such an effect becomes significant when it is contained at 0.005% or more, so it is preferably contained at 0.005% or more. However, when it is contained at more than 0.100%, the viscosity of the molten metal becomes too high, and defects such as poor fusion due to the weld bead not expanding increase. Therefore, when Al is contained, Al is preferably limited to 0.100% or less. More preferably, Al is 0.005% or more. More preferably, Al is 0.060% or less. More preferably, Al is 0.020% or less.

[0076] [Ca: 0.010% or less]

[0077] Ca combines with S in the molten metal to form high melting point sulfide CaS. CaS has a higher melting point than MnS, so it helps to suppress the occurrence of high temperature cracks in the weld metal. This effect becomes significant when it is contained at 0.001% or more. On the other hand, when it is contained over 0.010%, the arc becomes turbulent during welding, making it difficult to perform stable welding. Therefore, when Ca is contained, it is preferably limited to 0.010% or less. More preferably, Ca is 0.001% or more. More preferably, Ca is 0.008% or less.

[0078] [REM: 0.020% or less]

[0079] REM refers to rare earth elements such as Sc, Y, La, and Ce. REM is a strong deoxidizer and exists in the weld metal in the form of REM oxide. REM oxide becomes a nucleation site during solidification, thereby refining the grains and helping to improve the strength of the weld metal. This effect becomes significant when it contains more than 0.001%. However, when it contains more than 0.020%, the stability of the arc decreases. Therefore, when REM is contained, REM is preferably limited to less than 0.020%. It is more preferred that REM is more than 0.002%. It is preferred that REM is less than 0.018%. It is more preferred that REM is less than 0.010%.

[0080] [Remainder]

[0081] The balance other than the above components is composed of Fe and inevitable impurities. As inevitable impurities, for example, O, Sn, Sb, As, Pb, Bi, etc. are listed. It is preferred that the amount of O in the filler material is set to less than 0.15%, the amounts of Sn, Sb, and As are set to less than 0.005%, and the amounts of Pb and Bi are set to less than 0.0001%. In addition, as long as the above basic composition and optional components are met, elements other than these may be contained, and such an embodiment is also included in the technical scope of the present invention.

[0082] [Method for producing filling material]

[0083] Next, a method for producing the TIG welding filler material of the present invention will be described.

[0084] In the manufacture of the filler material of the present invention, except for using molten steel having the above-mentioned composition, there is no need to limit the manufacturing method thereof, and any commonly used manufacturing method of filler materials can be applied.

[0085] The filler material of the present invention is preferably, for example: a casting step is sequentially performed in which molten steel having the above-mentioned composition is melted in a common melting furnace such as an electric furnace, a vacuum melting furnace, and cast in a mold of a specified shape, followed by a heating step of heating the obtained steel ingot to a specified temperature; and a hot rolling step is performed on the heated steel ingot to form a steel raw material (rod-shaped) of a specified shape, and then a cold rolling step is performed on the obtained steel raw material (rod-shaped) twice or more (cold wire drawing) and an annealing step is performed at an annealing temperature of 900 to 1200°C as needed to form a welding wire of a desired size.

[0086] [Method for manufacturing welded joint]

[0087] A method for producing a welded joint portion by TIG welding a steel material as a base material using the above-mentioned filler material for TIG welding will be described.

[0088] By using the TIG welding filler material having the above composition, steel materials as base materials are butted, and the filler material is continuously supplied while blowing an inert gas, and welding is performed by generating an arc using a tungsten rod electrode, thereby producing a welded joint.

[0089] [Steel]

[0090] The steel material used as the base material is preferably a high-Mn steel material. The high-Mn steel material refers to a high-strength steel material for use at extremely low temperatures, and the Mn content is preferably 15.0 to 30.0% by mass. Specifically, the steel material has a basic composition containing, by mass%, C: 0.10-0.80%, Si: 0.05-1.00%, Mn: 15.0-30.0%, P: 0.030% or less, S: 0.030% or less, Cr: 2.5-15.0%, N: 0.120% or less, and the balance consisting of Fe and inevitable impurities, and in addition to the basic composition, one or two selected from Ni: 10.00% or less and Mo: 3.50% or less may be selected as optional components as needed, and one or two or more selected from V: 2.00% or less, Ti: 1.00% or less, and Nb: 1.00% or less may be selected, and one or two or more selected from Cu: 1.00% or less, Al: 0.100% or less, Ca: 0.010% or less, and REM: 0.020% or less may be selected.

[0091] As a method for producing high-Mn steel, there is a method of obtaining a steel material (steel plate) by hot rolling a steel raw material obtained through a conventional steelmaking process and a casting process, adjusting heating conditions, reduction ratio, etc., and then cooling the steel material. The thickness of the rolled steel plate is, for example, 3 to 100 mm.

[0092] Example

[0093] Hereinafter, the present invention will be further described based on Examples. However, the following Examples are merely examples for illustrating the present invention in more detail and do not limit the scope of the present invention.

[0094] Molten steel of the composition shown in Table 1 was melted in a vacuum melting furnace and cast to form a 1000 kg steel ingot. The obtained steel ingot was heated to 1200°C, hot rolled, then cold rolled, and annealed (900-1200°C) as needed to form a TIG welding filler material with a diameter of 2.0 mmφ and a length of 1000 mm.

[0095] Next, as a test plate, a high-Mn steel plate for use at extremely low temperatures (plate thickness: 12 mm) was prepared, and a 45° V-shaped groove was formed by butting according to JIS Z 3111, and TIG welding was performed using the obtained filler material to obtain a deposited metal in the groove. It should be noted that the high-Mn steel plate for use at extremely low temperatures used as a test plate used a steel plate having a composition consisting of 0.5% C-0.4% Si-25% Mn-3% Cr-balance Fe.

[0096] In TIG welding, filler materials (diameter 2.0 mmφ) of the composition shown in Table 1 are used, the electrode is a pure tungsten rod (3.2 mmφ), and preheating is not performed. The welding is carried out in a flat position with a current of 200 A (DCEN), a voltage of 12 V, a welding speed of 8 cm / min, an interpass temperature of 100-150°C, and a shielding gas of Ar.

[0097] [High temperature crack resistance]

[0098] After welding, the deposited metal was observed under an optical microscope (30 times) to determine the presence or absence of welding cracks. Welding cracks are high-temperature cracks. If cracks are confirmed, the high-temperature crack resistance is evaluated as "×". If no cracks are confirmed, the high-temperature crack resistance is evaluated as "○".

[0099] [Deposited Metal Characteristics]

[0100] According to JIS Z 3111, tensile test pieces (parallel portion diameter 6 mmφ) and Charpy impact test pieces (V-notch) of the deposited metal were cut out from the obtained deposited metal and subjected to tensile test and impact test.

[0101] [Tensile test: 0.2% yield strength (MPa)]

[0102] Tensile tests were performed on three pieces at room temperature, and the average of the obtained values ​​(0.2% yield strength) was taken as the tensile property of the deposited metal using the filler material. As described above, the target value of the present invention is set to a 0.2% yield strength of 400 MPa or more at room temperature.

[0103] [Impact test: Absorbed energy vE -196 (J)]

[0104] In addition, the Charpy impact test was performed on three pieces each, and the absorption energy vE at the test temperature of -196°C was calculated. -196 The target value of the present invention is set as the absorption energy vE as described above. -196 More than 28J.

[0105] The obtained results are shown in Table 2.

[0106] [Table 1]

[0107]

[0108] [Table 2]

[0109]

[0110] *) Based on JIS Z 3111

[0111] All of the examples of the present invention are welding materials that do not generate high-temperature cracks during welding and can obtain deposited metals that are excellent in high-temperature crack resistance.

[0112] In addition, the yield strength (0.2% yield strength) of all the examples of the present invention at room temperature is 400 MPa or more, and the absorbed energy vE of the Charpy impact test at a test temperature of -196°C is -196 The filler material having a strength of 28 J or more satisfies the above-mentioned target value, indicating that the filler material can obtain a weld metal having both high strength and excellent cryogenic toughness.

[0113] On the other hand, in the comparative examples outside the scope of the present invention, high temperature cracking occurred, the high temperature crack resistance decreased, or the 0.2% yield strength at room temperature was less than 400 MPa, and the absorbed energy vE -196 When the J is less than 28 J, a deposited metal having both the target strength and extremely low temperature toughness cannot be obtained.

[0114] Hereinafter, each comparative example will be described.

[0115] In filler No. 19, the P content was higher than the range of the present invention, so P segregated in the final solidification portion during welding, causing high temperature cracks.

[0116] In filler No. 20, the S content is higher than the range of the present invention, so MnS is generated, which may become the starting point of fracture. The absorption energy vE at the test temperature of -196°C is -196 If the J is less than 28 J, the desired excellent cryogenic toughness cannot be ensured.

[0117] In filler No. 21, the Cr content is lower than the range of the present invention, so the 0.2% yield strength of the deposited metal is less than 400 MPa, and the desired high strength cannot be ensured. In addition, the segregation of P to the final solidification portion during welding cannot be suppressed, so welding cracks (high temperature cracks) occur. In addition, the absorbed energy vE at the test temperature of -196°C is -196 If the J is less than 28 J, the desired excellent cryogenic toughness cannot be ensured.

[0118] In filler No. 22, the C content and the Mn content are higher than the range of the present invention. Therefore, carbides and Mn segregate to the final solidification portion during welding, causing welding cracks (high temperature cracks). In addition, carbides become the starting point of fracture. The absorbed energy vE at the test temperature of -196°C is -196 If the J is less than 28 J, the desired excellent cryogenic toughness cannot be ensured.

[0119] In filler No. 23, the C content is lower than the range of the present invention, so the 0.2% yield strength of the deposited metal is less than 400 MPa, and the desired high strength cannot be ensured. In addition, the absorbed energy vE at the test temperature of -196°C is -196 If the J is less than 28 J, the desired excellent cryogenic toughness cannot be ensured.

[0120] In filler No. 24, the Mn content is lower than the range of the present invention, so the stability of the austenite phase is low. Therefore, the absorption energy vE at the test temperature of -196°C is -196 If the J is less than 28 J, the desired excellent cryogenic toughness cannot be ensured.

[0121] In filler No. 25, the Mo content is higher than the range of the present invention, and Mo carbides that may become the starting point of fracture are generated. Therefore, the absorption energy vE at the test temperature of -196°C is -196 If the J is less than 28 J, the desired excellent cryogenic toughness cannot be ensured.

[0122] In filler No. 26, the Si content is higher than the range of the present invention, so Si segregates to the final solidification portion during welding, causing welding cracks (high temperature cracks). In addition, the absorbed energy vE at the test temperature of -196°C is -196 If the J is less than 28 J, the desired excellent cryogenic toughness cannot be ensured.

Claims

1. A method for manufacturing a welded joint, wherein: TIG welding of high Mn steel using TIG welding filler and non-consumable electrodes. The TIG welding filler material has the following composition: in terms of mass%, it contains C: 0.20-0.80%, Si: 0.15-0.90%, Mn: 15.0-30.0%, P: 0.030% or less, S: 0.030% or less, Cr: 6.0-15.0%, N: 0.120% or less, and the balance is Fe and inevitable impurities. The Mn content in the composition of the high Mn-containing steel is 15.0 to 30.0% by mass.

2. The method for manufacturing a welded joint portion according to claim 1, wherein: The composition of the TIG welding filler material further contains, in mass %, one or two selected from the group consisting of Ni: 10.00% or less and Mo: 3.50% or less.

3. The method for manufacturing a welded joint portion according to claim 1, wherein: The composition of the TIG welding filler material further contains, in mass %, one or more selected from the group consisting of V: ​​1.00% or less, Ti: 1.00% or less, and Nb: 1.00% or less.

4. The method for manufacturing a welded joint portion according to claim 2, wherein: The composition of the TIG welding filler material further contains, in mass %, one or more selected from the group consisting of V: ​​1.00% or less, Ti: 1.00% or less, and Nb: 1.00% or less.

5. The method for manufacturing a welded joint according to any one of claims 1 to 4, wherein: The composition of the TIG welding filler material further contains, in mass %, one or more selected from the group consisting of Cu: 1.00% or less, Al: 0.100% or less, Ca: 0.010% or less, and REM: 0.020% or less.

6. The method for manufacturing a welded joint according to any one of claims 1 to 4, wherein: The high-Mn steel has the following composition: in mass %, it contains C: 0.10-0.80%, Si: 0.05-1.00%, Mn: 15.0-30.0%, P: less than 0.030%, S: less than 0.030%, Cr: 2.5-15.0%, N: less than 0.120%, and the balance is Fe and inevitable impurities.

7. The method for manufacturing a welded joint portion according to claim 5, wherein: The high-Mn steel has the following composition: in mass %, it contains C: 0.10-0.80%, Si: 0.05-1.00%, Mn: 15.0-30.0%, P: less than 0.030%, S: less than 0.030%, Cr: 2.5-15.0%, N: less than 0.120%, and the balance is Fe and inevitable impurities.

8. The method for manufacturing a welded joint portion according to claim 6, wherein: The high Mn content steel material further contains, in addition to the above composition, one or two selected from the group consisting of Ni: 10.00% or less and Mo: 3.50% or less, in terms of mass %.

9. The method for manufacturing a welded joint portion according to claim 7, wherein: The high Mn content steel material further contains, in addition to the above composition, one or two selected from the group consisting of Ni: 10.00% or less and Mo: 3.50% or less, in terms of mass %.

10. The method for manufacturing a welded joint portion according to claim 6, wherein: The high Mn content steel material further contains, in addition to the above composition, one or more selected from the group consisting of V: ​​2.00% or less, Ti: 1.00% or less, and Nb: 1.00% or less, in terms of mass %.

11. The method for manufacturing a welded joint portion according to claim 7, wherein: The high Mn content steel material further contains, in addition to the above composition, one or more selected from the group consisting of V: ​​2.00% or less, Ti: 1.00% or less, and Nb: 1.00% or less, in terms of mass %.

12. The method for manufacturing a welded joint portion according to claim 6, wherein: The high Mn content steel material further contains, in addition to the above composition, one or more selected from the group consisting of Cu: 1.00% or less, Al: 0.100% or less, Ca: 0.010% or less, and REM: 0.020% or less, in terms of mass %.

13. The method for manufacturing a welded joint portion according to claim 7, wherein: The high Mn content steel material further contains, in addition to the above composition, one or more selected from the group consisting of Cu: 1.00% or less, Al: 0.100% or less, Ca: 0.010% or less, and REM: 0.020% or less, in terms of mass %.

Citation Information

Patent Citations

  • High-strength welded joints with excellent cryogenic impact toughness and wires for flux-cored arc welding therefor

    JP2017502842A

  • Solid wire for gas metal arc welding

    WO2020039643A1

  • Refractory steel material with excellent welded-joint toughness and process for producing the same

    CN101395292A

  • High strength steel material excellent in fatigue crack propagation property and manufacturing method therefor

    JP2015206112A

  • Tungsten inert gas welding material for high manganese steel

    KR1020160078621A